Trade Protection along Supply Chains - Chad P. Bown; Paola Conconi; Aksel Erbahar; Lorenzo Trimarchi (Center for Economic Studies and Ifo Institute (CESifo), 2020)
During the last decades, the United States has applied increasingly high trade protection against China. We combine detailed information on US antidumping (AD) duties — the most widely used trade barrier — with US input-output data to study the effects of trade protection along supply chains. To deal with endogeneity concerns, we propose a new instrument for AD protection, which combines exogenous variation in the political importance of industries with their historical experience in AD proceedings. We find that tariffs have large negative effects on downstream industries, decreasing employment, wages, sales, and investment. Our baseline estimates for 1988-2016 indicate that, due to AD protection against China, around 1.8 million US jobs were lost in downstream industries, with no significant job gains in protected sectors. When we extend the analysis to measures introduced under President Trump, we find that around 500,000 jobs were lost during the first two years of his term. We also provide evidence of the mechanisms behind the negative effects of protection along supply chains: AD duties decrease imports and raise production costs for downstream industries.
Keywords: F13; D57; 330; trade protection; supply chains; input-output linkages